THE CORRELATION BETWEEN LEARNING ENVIRONMENT IN SCHOOL AND THE INDEPENDENCE OF LEARNING WITH MATHEMATICS LEARNING OUTCOMES - Sandy Primanata; Suparyan Suparyan (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Many factors cause poor student learning outcomes. The learning environment in school and the independence of learning are some factors that correlate with learning outcomes. This study aims to determine a positive and significant correlation between the learning environment at school and the independence of learning with the results of learning mathematics for eight grade students of State Junior High School (SMP Negeri) 11 Yogyakarta year of 2017/2018. This study's population was all of SMP Negeri 11 Yogyakarta's eighth-grade students in the academic year 2017/2018. The number of students was 130 students. The experimental class and the sample class were taken by random sampling technique to each class. It was obtained of VIII C as the experimental class and VIII B as the sample class. The data collecting technique was done by test and questionnaire method. There are several types of instruments used in this research. There are validity tests, different power tests, and reliability tests. Analysis prerequisite tests were normality test, independent test, and linearity test. Data analysis for hypothesis tests were using correlation analysis and linear regression analysis. The first results showed a positive and significant correlation between the learning environment in school with the learning mathematics results by and , so obtained . The second results showed a positive and significant correlation between the independence of learning with the results of learning mathematics by and , so obtained. The third results showed a positive and significant correlation between the learning environment in school and the independence of learning with learning mathematics by and , so obtained. Double correlation coefficient (R) amount 0,8861 and coefficient of determination (R2) amount 0,7852 with the linear regression equation ie . Relative contribution of X1 is equal to 57,1280%, and X2 amount 42,8720% and relative contribution of X1 is equal to 44,8545% and X2 is equal to 33,6613%.